The Analysis of Domestic Travelers in Indonesia - Pratomo, Devanto Shasta (Universitas Negeri Semarang, 2017)
Indonesia is the largest archipelago country in the world, making one of popular tourist destinations in Southeast Asia region for both international and domestic holidays. The main objective of the study is to examine a wide range characteristics, including demographic, employment, and spatial characteristics for domestic travel in Indonesia.The method used in the study is descriptive analysis using the 2015 National Socio-Economic Survey (SUSENAS), which is used to explain some specific characteristics of domestic travelers in Indonesia. Some regression analysis using binary probit is also added to examine the determinants of domestic travel demand in Indonesia, measured by the probability to travel within the country. The result shows that, in general, domestic travelers in Indonesia are dominated by people who are living in urban areas, people who are aged 25-40 years old, highly educated, working as paid employees, and mostly originate from provinces in Java island.For specific purposes, people who are living in urban areas are more likely travel for holidays. Males are more likely travel for business compared to females. People who do have a job are more likely travel for business purposes, while people who are at school ages are the market for holiday travel.